2020
DOI: 10.1093/mnras/staa962
|View full text |Cite
|
Sign up to set email alerts
|

Free-form grale lens inversion of galaxy clusters with up to 1000 multiple images

Abstract: In the near future, ultra deep observations of galaxy clusters with HST or JWST will uncover 300 − 1000 lensed multiple images, increasing the current count per cluster by up to an order of magnitude. This will further refine our view of clusters, leading to a more accurate and precise mapping of the total and dark matter distribution in clusters, and enabling a better understanding of background galaxy population and their luminosity functions. However, to effectively use that many images as input to lens inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…It is natural to ask how image constraints affect the construction of a reliable lens model, by which it is meant that the source plane positions, redshifts, and/or magnification factors are accurately recovered. In one study, Ghosh et al (2020) analyzed simulations of clusters and found that introducing additional image constraints generally increased the accuracy of the mass map. To quantify the systematics of image constraints, Johnson & Sharon (2016) analyzed the strong-lensing model of a single simulation of a single cluster hundreds of times, differing only the amounts and types of lensing evidence.…”
Section: Introductionmentioning
confidence: 99%
“…It is natural to ask how image constraints affect the construction of a reliable lens model, by which it is meant that the source plane positions, redshifts, and/or magnification factors are accurately recovered. In one study, Ghosh et al (2020) analyzed simulations of clusters and found that introducing additional image constraints generally increased the accuracy of the mass map. To quantify the systematics of image constraints, Johnson & Sharon (2016) analyzed the strong-lensing model of a single simulation of a single cluster hundreds of times, differing only the amounts and types of lensing evidence.…”
Section: Introductionmentioning
confidence: 99%
“…(In the rest of the paper, we refer to H0LiCOW/SHARP/COSMOGRAIL/STRIDES collectively as TD-COSMO (Millon et al 2019)). Measurements of H 0 using time delay lenses also have been investigated by other collaborations (Paraficz & Hjorth 2010;Ghosh et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With increasing number of multiple images observed by future telescopes, see e.g. Ghosh et al (2020), our observationbased approach can equip an increasing lensing region with lensmodel-independent properties. Thereby, we will be able to replace assumption-based lens properties by evidence-based properties in a growing lensing region.…”
Section: Brief Outline Of Parts I To Vimentioning
confidence: 99%